Quality evaluation of university web portals: a student perspective. (1st January 2011) - Abdelhakim, Mohamed N.A.; Carmichael, James N.; Ahmad, Sayed Sayeed
Web portals have become popular among higher education institutions for a variety of reasons, chief among which is the competitive advantage such portals offer by facilitating a single point of access to multiple web services. Despite their critical importance, there has been relatively little research devoted to evaluating best-practice concepts in the design and content of web portals vis-à-vis user satisfaction. In an attempt to contribute to the abovementioned research domain, this paper proposes an evaluation instrument – the University Portal Usability Assessment Index (UPUAI) – which rates the quality of university portals in four areas, namely: (1) informational content, (2) transactional content, (3) website design and (4) student satisfaction. The UPUAI's evaluation procedures are discussed in detail and, by way of validation, the UPUAI was used to assess the quality of the web portals of the top five accredited universities in the United Arab Emirates. The conclusions and implications derived from this study are presented with a view to providing education professionals with a reliable measurement instrument to assess the quality of their university web portals.